Difference between Stūpa and Caitya in Ancient Time - Ranjitakar, Junu Basukala (Historical Journal, 2022)
Stūpa is the memorial sign of Buddhas, Pratyekabuddhas, arhatas, and Chakravarti kings. After their nirvāna, stūpa is raised with relics in the four intersecting paths. Caitya or cetiya indicates beautiful landscapes, holy trees, religious monuments, and respected persons, which are worthy to receive worship. Some major events of Buddha's life are also known as caitya. Buddha also used the word 'cetiya' for beautiful landscapes, which are found in Dīghanikāya. Pāli texts mention that stūpa and caitya are different from each other. Until the first century B.C., the stūpa and caitya are constructed differently and can also be differentiated from their inscriptions. The earlier Buddhist Sanskrt texts Saddharmapuṇḍarika and Prajñāpāramita have instructed monks, nuns, laymen, and laywomen to construct the stūpa and venerate the Stūpa through which they will be led to Buddhahood. Afterward, stūpa is also considered as one of the worshipping objects, which has later been a synonym with caitya.